2023
DOI: 10.1038/s41398-023-02490-7
|View full text |Cite
|
Sign up to set email alerts
|

LRFN5 and OLFM4 as novel potential biomarkers for major depressive disorder: a pilot study

Abstract: Evidences have shown that both LRFN5 and OLFM4 can regulate neural development and synaptic function. Recent genome-wide association studies on major depressive disorder (MDD) have implicated LRFN5 and OLFM4, but their expressions and roles in MDD are still completely unclear. Here, we examined serum concentrations of LRFN5 and OLFM4 in 99 drug-naive MDD patients, 90 drug-treatment MDD patients, and 81 healthy controls (HCs) using ELISA methods. The results showed that both LRFN5 and OLFM4 levels were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Furthermore, considering that antidepressant drugs were commonly used in clinical practice, both DN-MDD and DT-MDD were assigned to the training and testing sets. As our previous studies conducted [ 32 , 61 ], these two sets were used to evaluate the diagnostic generalizability of SCN11A. Here, we found that the SCN11A-based discriminative model had excellent diagnostic performance in diagnosing MDD patients in both the training set and testing set, which indicated that SCN11A might be a potential biomarker for diagnosing MDD.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Furthermore, considering that antidepressant drugs were commonly used in clinical practice, both DN-MDD and DT-MDD were assigned to the training and testing sets. As our previous studies conducted [ 32 , 61 ], these two sets were used to evaluate the diagnostic generalizability of SCN11A. Here, we found that the SCN11A-based discriminative model had excellent diagnostic performance in diagnosing MDD patients in both the training set and testing set, which indicated that SCN11A might be a potential biomarker for diagnosing MDD.…”
Section: Discussionmentioning
confidence: 55%
“…According to the Diagnostic and Statistical Manual of Mental Disorders-version IV criteria and the International Statistical Classification of Diseases and Related Health Problems criteria, 11 th revision, the diagnosis of MDD was validated by two qualified psychiatrists. The 17-item Hamilton Depression Rating Scale (HDRS) was used to assess the severity of depression in MDD patients [ 32 , 33 ]. All MDD patients enrolled from the First Affiliated Hospital of Chongqing Medical University’s Department of Psychiatry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation